Non-coding RNA-Associated Therapeutic Strategies in Atherosclerosis - Tang, Yuyan; Li, Huaping; Chen, Chen (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis has been the main cause of disability and mortality in the world, resulting in a heavy medical burden for all countries. It is widely known to be a kind of chronic inflammatory disease in the blood walls, of which the key pathogenesis is the accumulation of immunologic cells in the lesion, foam cells formation, and eventually plaque rupture causing ischemia of various organs. Non-coding RNAs (ncRNAs) play a vital role in regulating the physiologic and pathophysiologic processes in cells. More and more studies have revealed that ncRNAs also participated in the development of atherosclerosis and regulated cellular phenotypes such as endothelial dysfunction, leukocyte recruitment, foam cells formation, and vascular smooth muscle cells phenotype-switching and apoptosis. Given the broad functions of ncRNAs in atherogenesis, they have become potential therapeutic targets. Apart from that, ncRNAs have become powerful blueprints to design new drugs. For example, RNA interference drugs were inspired by small interfering RNAs that exist in normal cellular physiologic processes and behave as negative regulators of specific proteins. For instance, inclisiran is a kind of RNAi drug targeting PCKS9 mRNA, which can lower the level of LDL-C and treat atherosclerosis. We introduce some recent research progresses on ncRNAs related to atherosclerotic pathophysiologic process and the current clinical trials of RNA drugs pointed at atherosclerosis.